Multiple genetic loci define Ca++ utilization by bloodstream malaria parasites - Liana Apolis (BMC Genomics, 2019)
Abstract Background Bloodstream malaria parasites require Ca++ for their development, but the sites and mechanisms of Ca++ utilization are not well understood. We hypothesized that there may be differences in Ca++ uptake or utilization by genetically distinct lines of P. falciparum. These differences, if identified, may provide insights into molecular mechanisms. Results Dose response studies with the Ca++ chelator EGTA (ethylene glycol-bis(β-aminoethyl ether)-N,N,N′,N′-tetraacetic acid) revealed stable differences in Ca++ requirement for six geographically divergent parasite lines used in previous genetic crosses, with the largest difference seen between the parents of the HB3 x Dd2 cross. Genetic mapping of Ca++ requirement yielded complex inheritance in 34 progeny clones with a single significant locus on chromosome 7 and possible contributions from other loci. Although encoded by a gene in the significant locus and a proposed Ca++ target, PfCRT (P. falciparum chloroquine resistance transporter), the primary determinant of clinical resistance to the antimalarial drug chloroquine, does not appear to contribute to this quantitative trait. Stage-specific application of extracellular EGTA also excluded determinants associated with merozoite egress and erythrocyte reinvasion. Conclusions We have identified differences in Ca++ utilization amongst P. falciparum lines. These differences are under genetic regulation, segregating as a complex trait in genetic cross progeny. Ca++ uptake and utilization throughout the bloodstream asexual cycle of malaria parasites represents an unexplored target for therapeutic intervention.